Variations of Institutional Design for Empowered Deliberation - Carolina Johnson; John Gastil (Journal of Deliberative Democracy, 2015)
This paper lays out the practical and theoretical characteristics of formally empowered deliberation as a distinctive subset of deliberative processes. As part of a recent broad shift toward a more deliberative conception of democratic politics, participatory deliberative processes increasingly have been formally empowered as part of democratic governance. Governments have moved to delegate authority and deliberative responsibility from elite bodies to lay publics more quickly than scholars have been able to fully identify the implications of this institutionalization for the quality of both deliberation and democracy. This paper describes the emerging characteristics of formally empowered deliberation as a distinctive subset of deliberative processes, in which deliberation between members of the general public is given credible formal authority over policy development and decision making. We first develop a clearer conceptualization of empowered deliberation within the general trend toward participatory governance. We also review critical and supportive perspectives on empowered deliberation, making explicit tradeoffs inherent in the decision to develop an empowered deliberative process. Next, we identify four key dimensions of variation in the design of empowered deliberative institutions, in particular embeddedness in the social/ political context and the scope of authority of the deliberative decision. To illustrate these dimensions, we discuss key cases from around the world, noting which forms of empowered deliberation have seen less common innovation and documentation. Finally, we briefly consider how specific processes may become empowered or transform over time, as they transition from experimental or one-off pilot projects to recurring and institutionalized aspects of democratic governance.